A DENSITY MANAGEMENT DIAGRAM for EVEN-AGED EUCALYPTUS DUNNII STANDS in SOUTHERN BRAZIL - Krefta S.M.* (2021)
© Forest Research Institute MalaysiaDensity management diagrams (DMD) are graphic models that describe the forest stand dynamics, and they are extremely useful to regulate tree density. This study aimed to develop a DMD for Eucalyptus dunnii stands located in the municipality of Rio Negrinho, Santa Catarina, Brazil. Plots of 400 m2 were inventoried at the ages of 2, 3 and 4 years. The following variables were determined for the stands: the basal area per hectare, the number of trees per hectare and the geometric mean diameter. The Reineke model (1933) was fitted and its intercept value recalculated to define the maximum density line, reaching a determination coefficient of 0.5461. With the elaborated DMD of the current stand, a thinning can be simulated at 5.8 years with a cut at 7 years, taking into consideration a diametric increase of 2.41 cm. In addition, another scenario was simulated with thinning occurring at 4 and 6 years and a cut at 7.5 years. With the execution of this work, the DMD proved to be an efficient tool for the elaboration of forest management plans.